TINJAUAN SISTEMATIS KETERAMPILAN BERPIKIR KREATIF DALAM MATA PELAJARAN FISIKA - Riberio, Antonia Sofia Fortunato (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2023)
This study aims to obtain information on efforts to improve high school students creative thinking abilities in physics learning. The review method was chosen to obtain research journals with keywords in students' creative thinking abilities in high school physics learning with Google undergraduate reference sources, hands-on science, and research gates. Twenty-five journals were reviewed based on author (year), research design, creative thinking skills, and findings. Based on a study of 15 international and ten national articles, applying the Problem Based Solving learning model is the most widely used effort to improve creative thinking skills. In addition to Problem-Based Learning, several efforts can be made to enhance creative thinking skills, including implementing Project Based Learning, Creative Problem Solving, and developing physics learning tools. This research can contribute to the world of education, especially in evaluating physics learning.